2023
DOI: 10.1186/s13024-023-00598-4
|View full text |Cite
|
Sign up to set email alerts
|

A Trem2R47H mouse model without cryptic splicing drives age- and disease-dependent tissue damage and synaptic loss in response to plaques

Abstract: Background The TREM2 R47H variant is one of the strongest genetic risk factors for late-onset Alzheimer’s Disease (AD). Unfortunately, many current Trem2R47H mouse models are associated with cryptic mRNA splicing of the mutant allele that produces a confounding reduction in protein product. To overcome this issue, we developed the Trem2R47H NSS (Normal Splice Site) mouse model in which the Trem2 allele is expressed at a similar level to the wild-type Trem2 allele without evidence of cryptic spl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 74 publications
4
14
1
Order By: Relevance
“…While TREM2 knockout mice exhibit impaired developmental synaptic pruning (Filipello et al, 2018), our transplantation experiments show that human microglia carrying the TREM2 R47H/+ mutation can promote synapse loss in the mouse brain (Figure 5). These findings are broadly consistent with recent observations that TREM2 R47H mutations can promote neuron and synapse loss in vitro and in aged mice (Popescu et al, 2022;Tran et al, 2023). It should be noted, however, that Popescu et al (2022) also observed increased in vitro synaptosome uptake by TREM2 R47H/+ iPSC microglia, in contrast to our findings (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While TREM2 knockout mice exhibit impaired developmental synaptic pruning (Filipello et al, 2018), our transplantation experiments show that human microglia carrying the TREM2 R47H/+ mutation can promote synapse loss in the mouse brain (Figure 5). These findings are broadly consistent with recent observations that TREM2 R47H mutations can promote neuron and synapse loss in vitro and in aged mice (Popescu et al, 2022;Tran et al, 2023). It should be noted, however, that Popescu et al (2022) also observed increased in vitro synaptosome uptake by TREM2 R47H/+ iPSC microglia, in contrast to our findings (Figure 3).…”
Section: Discussionsupporting
confidence: 93%
“…Inflammatory responses by microglia in amyloid and tau models are generally dampened by the loss of TREM2 (Griciuc et al, 2019; Jay et al, 2017; Leyns et al, 2017). Studies examining TREM2 R47H mutations have often reported similar effects to knockout mutations, with R47H microglia in amyloid models exhibiting impaired plaque localization and response (Cheng‐Hathaway et al, 2018; Song et al, 2018; Tran et al, 2023). The apparent effects of the R47H mutation in tau mouse models have varied, with reports of increased or decreased tau seeding, microglial inflammation, and synaptic/cognitive effects (Gratuze et al, 2020; Leyns et al, 2019; Sayed et al, 2021; Tran et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…NfL, a marker for axonal injury/degeneration, has emerged as a potential biomarker for human AD 48 . Recent studies have also shown that plasma NfL concentration correlates well with plaque load in AD mouse models 49,50 . To gain insight about the influence of genetic diversity on axonal injury/disease progression, we quantified NfL in both the plasma and cortical insoluble fraction of mice of WT‐ and 5x‐CC strains at 4 and 12 months of age.…”
Section: Resultsmentioning
confidence: 99%
“…Recent efforts have produced a mouse model of the Trem2 R47H mutation in which bulk RNA-seq analysis has identi ed a unique Trem2 R47H induced interferon signature believed to be associated with microglia in response to Aβ pathology [22]. Activation of microglia signi cantly impacts neuronal function and can be neurotoxic [23], but resolving the cell type speci c impacts of this mutation on neuronal populations requires single-cell analysis.…”
Section: Introductionmentioning
confidence: 99%